Impact of HRM System strength and High performance work practices on Service Performance: Considering Mediating Mechanism - Adeel Javed; Osman sadiq Paracha (Journal of Management and Research, 2021)
The purpose of this paper is on how ability enhancing, motivation focused and opportunity creating high performance work practices and employee’s perception of HRM system strength relate to performance outcome i.e. branch service performance in a Bank’s settings. Furthermore, this paper explores the mediation effect of Line mangers ability, motivation and opportunity to implement human resource practices between the high performance work practices, perception of HRM system strength and service performance. Adopted a quantitative research design. Data collected from a sample of 761 employees across 380 different bank branches in Pakistan. Structural equational modeling technique was used to analyze the data. The result supported both content and process perspectives and the positive impact of ability, motivation and opportunity HR practices and HRM system strength on branch service performance. However, the mediation results indicated the partial acceptance. This study provides an empirical evidence of how high performance work practices and employee’s perception of HRM system strength influence branch performance of bank’s employees in developing nation context. The findings of this paper are expected to encourage researchers to be more thoughtful to the connection between organisational HRM system support and HR practices to improve performance within organisations by emphasizing the alignment between Line manager’s AMO and HPWP practices.